Delineation of Groundwater Potentials in Alkaleri And Environs, North-Eastern Nigeria (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Water is a necessity in every day of our life. In our homes, offices, schools, hospitals, markets, industries, and even in our personal journey, there is always the need for continual water supply to meet our basic water needs. The research is aimed at delineating groundwater potentials in Alkaleri and environs. The geological field mapping was carried out and different rock types were identified in the study area, which consist of Precambrian basement rocks (Migmatite Gneiss, Hornblende Granite, and Bauchite), and the tertiary sedimentary rock of Kerri-Kerri formation. The vertical electrical sounding method was used to delineate the groundwater potentials in the research area. A total of 30 vertical electrical sounding points was randomly selected and surveyed. The electrode configuration used for the work was Schlumberger array. Fourteen curves were identified in the study area. The result revealed that the transverse resistance values vary from 78.5 ?m2 to 7984.9 ?m2 with an average value of 2180.534?m2. The values of longitudinal conductance ranges from 0.002258 ? to 0.74634037 ? with an average of 0.1713455?. The transmissivity values range from 8.89 m2/day to 467.2 m2/day, average value of 100.3 m2/day. The hydraulic conductivity values range from 0.9m/day to 29.6m/day with mean value of 8.3m/day. Aquifer characteristics revealed that transmissivity and hydraulic conductivity showed low potential.
Keywords: delineating; groundwater potentials; alkaleri; geological; sedimentary; resistivity; aquifers